MacBook - Chambers, Mark L. (--For dummies., 2024)
For years, MacBook For Dummies has been making it easy to learn new technology. This new edition keeps the easy-to-follow instructions coming. Learn the basics of customizing your Dock and using desktop widgets. Then, figure out how to go on the internet, stream music, send instant messages, and more. Expert author Mark Chambers will show you how to navigate the macOS operating system and personalize your MacBook to your liking. And you'll learn your way around features like Stage Manager, Continuity Camera, SharePlay, and Handoff. Is this your first new computer in a while? MacBook For Dummies gives you the rundown on how to exist without an internal DVD drive. Whether you're a newbie or a Mac veteran looking for insider tips, this is the quick start guide for you.--